MEDICAL PROGRESS: Histamine and the Antihistaminic Drugs - Keeney, Edmund L. (1950)
The tissues affected by histamine and anaphylactic reactions are identical. Epinephrine antagonizes the action of histamine by acting on effector cells in a direction opposite to that of histamine. The so-called antihistaminic drugs block rather than antagonize the action of histamine. The injection into the human body of epinephrine or certain antihistaminic substances provokes the release of histamine and thereby produces a rise in the histamine blood level. There is a remarkable conformity of potency of antihistaminics as determined by Dale experiments and by histamine intoxication experiments in the intact guinea pig. Neoantergan, Pyribenzamine and Histadyl are usually superior to other compounds when potency is assayed by these methods. All antihistaminics provide similar protection again animal anaphylaxis. Larger doses are necessary to protect against anaphylaxis than against histamine intoxication. The differences in potency as determined by Dale experiments and histamine experiments in animals are not found in clinical use. One compound is not generally superior to all others in the treatment of any one or several allergic disorders. The antihistaminic drugs are beneficial in the symptomatic treatment of allergic rhinitis, acute urticaria and angioneurotic edema, and mild non-infective bronchial asthma. Their effectiveness in the management of moderately severe and severe non-infective bronchial bronchial asthma; infective bronchial asthma; migraine; atopic dermatitis (disseminated neurodermatitis), and pruritus of skin disorders other than acute urticaria and angioneurotic edema, is not worthy of particular commendation. The size of the dose of any antihistaminic substance influences the incidence of but not the type of side-effect that may accompany its usage. The quality of side effects varies according to the drug, although there is an individuality of response for each patient which must be reckoned with. In selecting an antihistaminic compound it is necessary to consider the percentage of cases in which side effects occur, as well as the percentage of good results. Optimal results are obtained by employing combinations of compounds and changing from one to the other as the case demands.